Free vascularized fibular graft in patient with skeletal defect after neurofibroma surgical excision of forearm - Persada Isma, Satria Pandu; Budi Santoso, Agung Riyanto; Junus Huwae, Thomas Erwin Christian; Irsan, Istan Irmansyah; Purbiantoro, Yudhi (International Journal of Research in Medical Sciences, 2019)
The free vascularized ﬁbular graft has been successfully applied as a reconstruction option in patient with large secondary skeletal defects result from excision of pathologic tissue after neurofibroma surgical excision. It provides a strong cortical strut for reconstruction of defects, so that the free vascularized ﬁbular graft is ideal for ulna reconstruction. A 22-year-old male with lump in his right forearm for 3 months previously which become bigger and more painful. There was also sings of ulnar nerve disfunction. From the CPC result, we diagnosed forearm neurofibroma. We performed wide excision and reconstruction using free vascularized fibular graft. On the last follow up, the active and passive ranges of motion (ROM) of 4th and 5th metacarpal was measured with the help of a goniometer. The ulnar neurological state was tested by manual testing and graded on the Medical research council (MRC) scale. Four weeks after surgery, the operation wound at the right forearm and right lower leg was good and no infection signs. The graft viability was good with compromised vascularity. The post-operative passive and active ROM of the 4th and 5th metacarpal able did full extend. The post-operative sensoris level of the ulnar area improved from pre-operative sensoris level. Post-operative follow-up, in the early period (up to 6 weeks) we monitor the graft viability. Our case reported good result in the operation wound, the graft viability, the passive and active ROM of the 4th and 5th metacarpal and the sensoris level of the ulnar area.